THE DEBATES SURROUNDING THE ACCOMMODATION OF ISLAMIC ADULTERY CRIME AND PUNISHMENT INTO INDONESIAN CRIMINAL CODE (JOURNAL OF INDONESIAN ISLAM, 2016)
The current bill of Indonesian Criminal Code is going to be sanctioned in no time. In the draft, the crime of adultery has leaned to Islamic criminal law in many respects, although the punishment is far more lenient. The definition of adultery has been broadened to cover fornication and cohabitation. Heavier punishment is applicable although not as severe in Islamic criminal law. When the draft is sanctioned, the Code arguable will be deemed more Islamic. This paper will discuss adultery as a crime in Indonesian Criminal Code as it is inherited from the Dutch, Islamic criminal law, and its stipulation in the Draft of Indonesian Criminal Code. The article also highlights the controversy surround the issue along the way.